Comment on “Widespread RNA and DNA sequence differences in the human transcriptome” - Pickrell, Joseph K. (Science, 2012)
Li et al. [1] reported over ten thousand mismatches between mRNA and DNA sequences from the same individuals, which they attributed to previously unrecognized mechanisms of gene regulation. We found that at least 88% of these sequence mismatches can likely be explained by technical artifacts such as errors in mapping sequencing reads to a reference genome, sequencing errors, and genetic variation.